2016
DOI: 10.1088/0967-3334/37/6/751
|View full text |Cite
|
Sign up to set email alerts
|

In vivoquantification of intraventricular hemorrhage in a neonatal piglet model using an EEG-layout based electrical impedance tomography array

Abstract: Intraventricular hemorrhage (IVH) is a common occurrence in the days immediately after premature birth. It has been correlated with outcomes such as periventricular leukomalacia (PVL), cerebral palsy and developmental delay. The causes and evolution of IVH are unclear; it has been associated with fluctuations in blood pressure, damage to the subventricular zone and seizures. At present, ultrasound is the most commonly used method for detection of IVH, but is used retrospectively. Without the presence of adequa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 36 publications
0
16
0
Order By: Relevance
“…Besides the cranium and blood, the injection site may also result in the different impedance changes within brain. For instance, when the blood was injected into cerebral ventricle [19] or subarachnoid space [20], which is full of CSF, the corresponding impedance gain was observed on EIT images; the possible reason may lie in the lower impedance of CSF than blood. Thus in future study, it is necessary to be aware of the blood injection site and consider the interaction among blood, parenchyma, and CSF, as well as their effects on the relevant impedance changes of brain.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides the cranium and blood, the injection site may also result in the different impedance changes within brain. For instance, when the blood was injected into cerebral ventricle [19] or subarachnoid space [20], which is full of CSF, the corresponding impedance gain was observed on EIT images; the possible reason may lie in the lower impedance of CSF than blood. Thus in future study, it is necessary to be aware of the blood injection site and consider the interaction among blood, parenchyma, and CSF, as well as their effects on the relevant impedance changes of brain.…”
Section: Discussionmentioning
confidence: 99%
“…This finding was also observed by Dowrick et al [17] who injected autologous blood into rat brain with the closed cranium. On the other hand, Sadleir et al [18] and Tang et al [19] employed EIT to monitor ICH in the open/closed cranium pig model of intraventricular hemorrhage and found that brain impedance increased with the amount of blood injected. Dai et al [20] also reported an increase in brain impedance when autologous blood was injected into subarachnoid space in the closed cranium pig models.…”
Section: Introductionmentioning
confidence: 99%
“…10 Bioimpedance is an increasingly used tool with multiple medical applications, including estimating volume status in patients with heart failure, detecting cancer, and monitoring patients for internal bleeding complications after percutaneous femoral access. [11][12][13][14] In these scenarios, bioimpedance has proved accurate in detecting small changes in tissue composition.…”
Section: Discussionmentioning
confidence: 99%
“…There is a wide range of animal models used for research in PHH of prematurity and germinal matrix hemorrhage (reviewed in [ 233 , 234 ]), and no single animal model will be suitable for all biological questions. Most studies involve experimental induction of IVH in mice [ 67 , 191 , 235 ], rats [ 182 , 185 , 202 , 236 – 243 ], rabbits [ 244 250 ], cats [ 251 ], dogs [ 252 , 253 ], sheep [ 254 ], and pigs [ 255 258 ]. While the majority of these in vivo studies have employed intraventricular injection of whole blood or blood products, others have used alternative approaches [ 67 , 247 , 259 261 ].…”
Section: Moving Basic Science Discoveries Into Clinical Practicementioning
confidence: 99%